Comparing repeated end range movements and Kinesio taping effects on head and neck movement pattern and discomfort in smartphone users - Naeimi, Ehsan; Olyaei, Gholam Reza; Hadian, Mohammad Reza; Talebian, Saeed; Khanmohammadi, Roya (Journal of bodywork and movement therapies, 2024)
Using smartphones has increased exponentially, especially after the COVID-19 pandemic. However, there is a relationship between neck flexion angle during working with a smartphone and neck musculoskeletal disorders. Therefore, this study compares the effect of Kinesio taping and Repeated End Range Movements (RERM) on head and neck flexion angles changes during texting and discomfort after texting with a smartphone. Twenty-four smartphone users participated in this cross-over study. All of 24 subjects were experimented with the control, RERM and taping conditions. They filled Numeric Rating Scale questionnaire before and after 30 min of texting. In addition, their head and neck flexion angles were measured during the task by photogrammetry. In the RERM group, individuals felt significantly less discomfort than the control group after the task (P = 0.032). Although the slope of average head and neck flexion angles linear regression lines of all the three groups was positive before the break time, it became negative in the taping and control groups after the break time. In addition, the linear regression of average head and neck flexion angles of the RERM group was significantly different (P < 0.001). RERM can effectively maintain normal head and neck movement pattern during and reduce neck discomfort after texting on smartphone.